TRIGONOMETRICAL APPROACH TO CURVED PSEUDO ELASTIC IMPEDANCE (CPEI) AND PSEUDO ELASTIC IMPEDANCE - LITHOLOGY (PEI-L) ATTRIBUTE FOR RESERVOIR CHARACTERIZATION OF LOWER TERUMBU FORMATION, - Wahyuzi, A.Meickloni
The East Natuna Basin is one of the basins that produce hydrocarbons, especially gas, in Indonesia. The "EL CLASICO" field is located in the East Natuna Basin and this research focuses on the Lower Terumbu Formation. The lithology of this formation is an interchange between shale and thin sandstones, so a method is needed that be able to separate two lithologies well. Analysis of well log data shows AI and VpVs Ratio are sensitive elastic parameters. The seismic method of model based inversion was done by AI analysis and extended elastic impedance for generate VpVs Ratio. The results of elastic parameter inversion data will be biased for non-dominant value of AI-VpVs Ratio and Elastic parameter results usually show linear relationship derived through regression, while petrophysical parameters exhibit a nonlinear trend. With that in mind, reservoir characterization is done utilizing curved-pseudo elastic impedance (CPEI) and pseudo elastic impedance – lithology (PEI-L). This reservoir characterization approach utilized petrophysical parameters that are going to be analyzed, which consist of porosity through PEI-L Attribute to include the compaction trend and water saturation through CPEI Attribute to include fluid trend. CPEI and PEI-L attributes in this research is conducted in AI-VpVs domain. The creation of CPEI and PEI-L attributes is generated utilizing trigonometrical approximation and maximum correlation angle analysis in terms of the targeted petrophysical parameter. The CPEI attribute has a correlation of 0.70187 to water saturation and PEI-L attribute has a correlation of -0.8634 to porosity. The results of CPEI dan PEI-L are transformed into volume porosity and water saturation. The result showed that the low value of AI, VpVs Ratio, CPEI, PEI-L,water saturation, and as well as high porosity indicate that the "EL CLASICO" field in the Lower Terumbu Formation is a porous shally sandstone and have indication filled by hydrocarbon fluids.